Experiential Learning Implementation in Rice Agriculture Education Program at Imah Urang Educational Tourism - Wijaya, Yeni; Hermawan, Yudan (FKIP - Universitas Riau, 2025)
Karawang, an agrarian area located in West Java, has recently experienced a rapid industrial transformation that has led to a breakdown in intergenerational transmission of local farming knowledge and ecological values. As a response to this situation, Imah Urang Educational Tourism implemented a rice agriculture education program situated in outdoor learning experiences that uses Kolb’s (2015) Experiential Learning framework. The aim of the current study is to describe the experiential learning that occurs in the program, and examine how each phase of the cycle (Concrete Experience, Reflective Observation, Abstract Conceptualization, and Active Experimentation) informs development of agrarian, ecological and cultural values. Data were collected using a descriptive qualitative method where observation, interviews with key stakeholders and documentation provided the basis of analysis of findings. The findings demonstrated that the program successfully encouraged participation in experiential activities and evoked empathy for farmers and ecological thinking, as well as valuing culture. The study concludes that non-formal educational tourism that uses an experiential educational approach in agrarian areas impacted by industry can act as a practical educational model for sustainability learning.